n the work of «It» magik realism, the boundaries between the real and mystical worlds - Ochilov, Ulugbek (The Lingua Spectrum, 2025)
Stephen King‘s «It» is a prime example of magical realism where ordinary life and mystical elements seamlessly merge. This article analyzes the manifestation of magical realism in «It», focusing on how children’s fears and their fight against evil are depicted. Through examples, the article explores King‘s writing technique and how he blurs the boundaries between reality and the mystical world.